Sosialisasi Dan Pelatihan Penyusunan Laporan Keuangan Menggunakan Aplikasi Digital “Si Apik” Pada Ukm Dusun Kranon - Syafira Dhuha Muslim; sumaryanto (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
This Community Service activity aims to provide knowledge to SME players in making financial reports in accordance with applicable standards by utilizing digital applications made by Bank Indonesia (BI), namely the Financial Information Recording Application Information System (SI APIK), so that the preparation of financial reports can be made easily. Financial reports are very important in running a business, it can control business operating costs. The implementation of this socialization and training is expected to help solve problems faced by SMEs regarding the preparation of business financial reports. The initial target of this activity was to invite SME players in Kranon Hamlet. The method of implementing this activity is carried out in 3 stages, namely material presentation or socialization, preparation of financial reports using the SI APIK digital application, and discussion. The technique of collecting data is by giving a questionnaire (pre-test) to the participants. The results of the questionnaire before the socialization and training were faced with a lack of understanding and knowledge about financial reports. Participants considered financial statements to be difficult and complicated. There are also those who think that science can only be learned by highly educated people and students. To deal with the problems and obstacles faced by SMEs, when the implementers conduct socialization and training on financial reports using the Si Apik digital application. The result of this community service is an increase in the understanding and interest of business actors regarding the preparation of good and correct financial reports.